2017
DOI: 10.1111/1755-5922.12314
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic impact of pulmonary vasodilators on single ventricle physiology

Abstract: Summary Introduction The Fontan procedure is the palliative procedure for single ventricle physiology. Pulmonary resistance plays a key role in the success of this operation. There are conflicting data concerning the impact of pulmonary vasodilators on survival and functional capacity among Fontan patients. Aim The aim of this retrospective, single‐center, nonrandomized study was to investigate the potential effect of pulmonary vasodilators on pulmonary vasculature in Fontan patients. Method Twenty‐seven patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In such conditions, a pharmacological target strategy using pulmonary vasodilators is of interest. Recent studies have evaluated sildenafil in SV patients and suggested it would decrease pulmonary resistance, improve ventricular filling, and increase exercise tolerance, with low toxicity and good clinical tolerance . A recent randomized study of 19 patients, using pressure/volume curves during cardiac catheterization, and two recent echography studies showed an improvement of ventricular function under sildenafil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such conditions, a pharmacological target strategy using pulmonary vasodilators is of interest. Recent studies have evaluated sildenafil in SV patients and suggested it would decrease pulmonary resistance, improve ventricular filling, and increase exercise tolerance, with low toxicity and good clinical tolerance . A recent randomized study of 19 patients, using pressure/volume curves during cardiac catheterization, and two recent echography studies showed an improvement of ventricular function under sildenafil.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a TPG above 5 mmHg avoids enrolling patients with isolated ventricular or atrio‐ventricular valve dysfunction. Indeed, diastolic ventricular dysfunction seems to be aggravated by pulmonary vasodilators and may explain discrepancies in the results observed in previous studies . We purposely did not use pulmonary vascular resistance to define patients eligible to the SV‐INHIBITION trial, given the known difficulties to accurately measure pulmonary blood flow in SV physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly surprising given the concerns regarding underlying diastolic dysfunction in single ventricle patients. Castaldi et al . reported a significant increase in PAWP following vasodilator therapy in individuals > 5 years post‐Fontan operation with patients having worst outcomes in their cohort (heart transplantation or death) having marked increases in PAWP post‐vasomodulator therapy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Finally, a study of 6 Glenn and 12 Fontan patients showed improvement in pulmonary compliance and Nakata index of pulmonary artery size after treatment with sildenafil (n=1), bosentan (n=16), or ambrisentan (n=1). 20 As illustrated, much of the literature has focused on the Fontan population because earlier failure of single-ventricle palliation either after neonatal palliation (depending on the anatomy and amount of pulmonary blood flow after birth) or Glenn operation is more commonly related to ventricular dysfunction or other inherent patient risk factors. In addition, early attrition from the single-ventricle pathway related to pulmonary vascular disease may be better treated with heart transplantation as PVR in this group is rarely high enough to preclude transplantation and long-term outcomes in high-risk single-ventricle patients remain poor.…”
Section: Failing Fontan Populationmentioning
confidence: 99%